Zinc picolinate supplementation decreases oxidative stress in rainbow trout (Oncorhynchus mykiss) - Kucukbay, Fatumetuzzehra; Yazlak, Hasan; Şahin, Nurhan; Tuzcu, Mehmet; Cakmak, Mehmet Nuri; Gurdogan, Fuat; Şahin, Kazım (Elsevier, 2006)
The effect of zinc picolinate (ZnPic) supplementation at various levels (0, 30, 60 mg/kg of diet) on growth, feed intake, feed efficiency and concentrations of malondialdehyde (MDA), Zn, Cu and Mn, and serum alkaline phosphatase (ALP) activity of rainbow trout was evaluated. Ninety 0+ y-old rainbow trout were randomly assigned to 3 treatment groups, 2 replicates of 15 fish each. The fish were fed either a basal diet or the basal diet supplemented with either 30 or 60 mg of Zn/kg of diet. Body weight gain, feed intake and feed efficiency were not significantly influenced by the dietary zinc picolinate supplementation. Serum alkaline phosphatase activity concentration linearly increased (P=0.01), whereas serum, liver and whole body malondialdehyde (MDA) concentrations linearly decreased as dietary ZnPic supplementation increased (P=0.001). Increasing dietary zinc supplementation linearly increased serum (P=0.01) and whole body Zn concentrations (P=0.05). However, serum and whole body Cu and Mn concentrations did not change as dietary ZnPic supplementation increased. Results of the present study indicate that zinc picolinate supplementation significantly decreased oxidative stress in rainbow trout and did not impact growth or feed consumption. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: zinc picolinate; malondialdehyde; alkaline phosphatase; rainbow trout